Homocysteine related vitamins and neuropsychiatric disorders - Bolander-Gouaille, Christina (Springer)
During the last 15 years the research on homocysteine and the vitamins involved in its metabolism has become very dynamic. About 1,500 publications on the subject are now published each year. The research has long mainly focused on the association between homocysteine and cardiovascular disease, but also pregnancy complications/ fetal malformations. There is, however, an increasing interest in the connection between the homocysteine metabolism and neuropsychiatric disease with a steeply increasing number of publications. In particular, the association between homocysteine metabolism and cognitive decline/dementia attracts much interest. If simple, non-toxic homocysteine-lowering treatment with vitamins can reduce the incidence of, or delay the onset of dementia, it would have an enormous impact in societies with a rapidly increasing number of elderly at risk for dementia. This book summarises the research within the neuropsychiatric field, but also gives an overview of the underlying biochemistry and of diagnostic aspects. About 1,000 references are given. Christina Bolander-Gouaille, a pharmacist, has for over 10 years specialised in writing reviews/monographs on homocysteine and related vitamins. This is her third book in a series edited by Springer Verlag. This book, however, is written in collaboration with Teodoro Bottiglieri, who is director of neuropharmacology and senior research scientist at Baylor University, Institute for Metabolic Diseases in Dallas, USA. What is homocysteine? - Homocysteine metabolism - How can homocysteine be neurotoxic? - Why do homocysteine levels increase? - Neuropsychiatric conditions associated with hyperhomocysteinemia - Clinical impact of enzyme defects - When and how to check homocysteine levels? - How to interpret the test results and how to handle hyperhomocysteinemia?